Analisis Minat Penggunaan Fintech Berdasarkan Konsep ECT-IS - Dicky Andriyanto; Irvan Ali Mustofa; Fandi Prasetya (Universitas Islam Balitar, 2022)
This research aims to obtain empirical evidence regarding the behavior intention in using Fintech as electronic-based financial access through the ECT-IS model combined with data security system. The sampling method for this research using judgment sampling. The survey method is carried out in the process of collecting data. Empirical evidence of research explains that perceived usefulness has a positive and significant effect on the level of satisfaction and behavior intention. The effect confirmation of use on perceived usefulness and individual satisfaction has positive and significant effect. The effect of data security systems on individual satisfaction is positive and significant. Likewise, the level of individual satisfaction have significant effect on behavior intention in using Fintech.